Supply Chain Management with SAP APO™ Structures, Modelling Approaches and Implementation of SAP SCM™ 2008 - Dickersbach, Jörg Thomas (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The Advanced Planner and Optimiser (SAP APOTM) is the software from SAP dedicated to supply chain management. This book provides an overview about the supported SCM processes and explains how to implement SAP APOTM in a company. It is written from a long years' experience in implementation projects and aims to provide project managers and team members with the necessary know how for a successful implementation project. The focus of the book lies in introducing modelling approaches and explaining the structure and interdependencies of systems, modules and entities of SAP APOTM based on the release SAP SCMTM 2008. Another concern is the integration with SAP ERPTM, both technically and from a process point of view. Since SAP APOTM projects differ significantly from other SAP projects, some key issues and common mistakes concerning project management are mentioned as well.